Insider Ownership, Free Cash Flow, And Collateralizable Assets On Dividend Policy - Maulina Dyah Permatasari; Adibah Yahya; Safira Nur Anisa (Proceeding International Pelita Bangsa, 2023)
The dividend is a portion of earnings decided and approved by the shareholders' meeting for distribution among shareholders. Determining the dividend distribution policy can pose challenges for companies due to conflicting interests between investors and company management. A key issue faced by companies is whether profits should be reinvested in business development, used to pay creditors, or distributed as dividends. This research aims to investigate the impact of Insider Ownership, Free Cash Flow, and Collateralizable Assets on the dividend policy of manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2021. The dividend policy is measured using the dividend payout ratio, and the study relies on secondary data collected through purposive sampling. The analytical method employed is panel data regression analysis. The findings of the study indicate that Insider Ownership has a significant influence on the dividend policy, while Free Cash Flow and Collateralizable Assets do not exhibit any significant effect on the dividend policy. However, when considering all three factors together, Insider Ownership, Free Cash Flow, and Collateralizable Assets collectively impact the dividend policy.